Pengaruh Nilai Tukar dan Jumlah Uang Beredar terhadap Inflasi di Indonesia Tahun 2020-2022 - Aliva Riwana; Holili; Rudy Haryanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Inflation is one of the causes of an economic crisis in a country. Inflation is a continuous increase in prices over a certain period of time. The quantitative approach is the method used in this research with a population of 36 taken from monthly data for 2020-2022. Sampling used saturated samples, namely 36. The tests used multiple linear regression, classical assumption tests, partial tests and simultaneous tests. After carrying out a series of analyzes, a result was obtained that in part, both the exchange rate variable and the money supply variable had a significant influence on inflation in Indonesia. Then simultaneously the exchange rate and money supply have a significant influence on inflation in Indonesia. These two independent variables influence inflation by 44.5%. Inflation can be suppressed by maintaining the stability of the rupiah exchange rate as well as the amount of money circulating in society